^{2}-3X + 2y

^{2}+4y -20 = 0

^{2 }- 3/2X ) + 2 ( Y

^{2}+ 2Y ) = 20

^{2}- 3/2 X + 9/16 ) + 2 ( Y

^{2}+ 2Y + 1 ) = 20 +9/8 + 2

^{2}+ 2 ( Y + 1 )

^{2 }= 185/8

^{2}+ ( Y + 1 )

^{2}= 185/8

The center of the circle is (?,?)

The radius of the circle is ?

Tutors, sign in to answer this question.

Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...

2 X^{2} -3X + 2y^{2} +4y -20 = 0

2 ( x^{2 }- 3/2X ) + 2 ( Y^{2} + 2Y ) = 20

2 ( X^{2} - 3/2 X + 9/16 ) + 2 ( Y^{2} + 2Y + 1 ) = 20 +9/8 + 2

2 ( X - 3/4)^{2} + 2 ( Y + 1 ) ^{2 } = 185/8

( X - 3/2)^{2} + ( Y + 1 )^{2} = 185/8

Center ( 3/4, -1) r = √(185/8) = 4.81

The equation of the circle has form:

(x-a)^{2}+(y-b)^{2}=R^{2}, where point (a,b) is the center of the circle, R is its radius.

In your case,

2x^{2}-3x+2y^{2}+4y-20=0 Divide both sides by 2 to get:

x^{2}-3/2*x+y^{2}+2y-10=0; Let us work on y-coordinate of the center first.

y^{2}+2y-10=y^{2}+2y+1-11=(y^{2}+2y+1)-11=(y+1)^{2}-11. Now we made y-part in the form (y-b)^{2}, here b=-1.^{
}

Back to the x-part;

x^{2}-3x/2+(y+1)^{2}-11=0; (x^{2}-2*3/4*x+9/16)-9/16+(y+1)^{2}-11=0;

Move -9/16 and -11 to the right side to get:

(x^{2}-2*3x/4+9/16)+(y+1)^{2}=11+9/16; ⇔ (x-3/4)^{2}+(y+1)^{2}=185/16;

This is now a canonical form of the equation of a circle. **Its center is at the point (3/4;-1)**

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.